(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
Major residential districts as well as public buildings, for a total of about fifty dwellings, characterize the city of Milan during the Roman period; this fact is better documented in the Northwestern sector of the city, then occupied by the Imperial Palace. The dating of the houses is framed in the second half of the first Century BC until the fourth or fifth Century AD. The extension of the domus is unknown because of the incomplete remains that could be excavated; therefore it is difficult to propose a general framework regarding the layout of the dwellings, the distribution of the rooms and their function. However, the preserved remains, including building structures, decoration - paintings and mosaics -, materials finds (such as pottery, glass, marble) reveal the urban and cultural development of Mediolanum. In the western area, just outside the city limit, there are many building remains of Roman houses where mosaic pavements and frescoes testify the high level of the constructions.